Teaching Note: Reflections of a Transgender Medievalist - Davi, Angelique (Radical Teacher, 2015)
I am a gender-bending lesbian who teaches Beowulf at a business university. In this piece, I reflect on an incident that reminds me I have little control over where and when my identity becomes more or less prominent for my students. Because the incident took me by surprise, I failed to capitalize on a teachable moment; this piece is my attempt at making sense of that failure.